Mehr weibliche Business Angels führen zu mehr Startup Gründerinnen - Alexandra Wuttig; Susanne Theresia Weber (IUBH Internationale Hochschule, 2020)
– Female entrepreneurs belong to the underrepresented groups and are thereby an economically unused potential. 84.9% of startup founders are male, so women are still underrepresented in the field of startups. Female founders, just like their male colleagues, have to master the challenges of start-up financing and networking with the established economy. However, studies have found that male investors tend to provide money to male founders and many female founders complain about lack of capital. It can be worthwhile to invest in female founders. Female founders achieve better turnovers and are on average more successful than purely male teams of founders. For this early stage phase of the business start-up, capital procurement by business angels is the preferred method of financing. Parallel to the low number of female company founders, the number of female business angels is also very low. According to a recently published study by the European Commission, only 8% of business angels in Europe are female. In 2019, the Forbes list of top investors included only 12 women out of 100 listed investors, in 2018 there were even only nine. Thus, an increase in female business angels also means a strengthening and diversification of the female start-up landscape. This promotion of female entrepreneurship thus benefits not only the women themselves, but the German economy as a whole. The aim of the study was to find out the reasons for the low number of female business angels in Germany and to present suitable measures that could lead to an increase in investment by women.
Keywords: O4; G2; 650; Entrepreneurship; Finanzen und Kapital; Gender Studies; Business Angels; Venture Capital; Frauenförderung